Sources of variation for indoor nitrogen dioxide in rural residences of Ethiopia - Kumie, Abera (BioMed Central, 2009)
BACKGROUND: Unprocessed biomass fuel is the primary source of indoor air pollution (IAP) in developing countries. The use of biomass fuel has been linked with acute respiratory infections. This study assesses sources of variations associated with the level of indoor nitrogen dioxide (NO(2)). MATERIALS AND METHODS: This study examines household factors affecting the level of indoor pollution by measuring NO(2). Repeated measurements of NO(2 )were made using a passive diffusive sampler. A Saltzman colorimetric method using a spectrometer calibrated at 540 nm was employed to analyze the mass of NO(2 )on the collection filter that was then subjected to a mass transfer equation to calculate the level of NO(2 )for the 24 hours of sampling duration. Structured questionnaire was used to collect data on fuel use characteristics. Data entry and cleaning was done in EPI INFO version 6.04, while data was analyzed using SPSS version 15.0. Analysis of variance, multiple linear regression and linear mixed model were used to isolate determining factors contributing to the variation of NO(2 )concentration. RESULTS: A total of 17,215 air samples were fully analyzed during the study period. Wood and crop were principal source of household energy. Biomass fuel characteristics were strongly related to indoor NO(2 )concentration in one-way analysis of variance. There was variation in repeated measurements of indoor NO(2 )over time. In a linear mixed model regression analysis, highland setting, wet season, cooking, use of fire events at least twice a day, frequency of cooked food items, and interaction between ecology and season were predictors of indoor NO(2 )concentration. The volume of the housing unit and the presence of kitchen showed little relevance in the level of NO(2 )concentration. CONCLUSION: Agro-ecology, season, purpose of fire events, frequency of fire activities, frequency of cooking and physical conditions of housing are predictors of NO(2 )concentration. Improved kitchen conditions and ventilation are highly recommended.